BABAD BLAHBATUH: ANALISIS STRUKTUR DAN FUNGSI - Junia Wardani, Ni Luh Gede; Duana Sutika, I Nym; Ngurah Sulibra, I Kt (Humanis, 2016)
Babad is one of the Balinese cultural heritage which is still alive and thriving in Bali. Babad also contain structure patterns and social function of  literature. Babad Blahbatuh discussed using the theory of the structure and function. this study based on the theory Teeuw. The methods used are: (1) collecting data phase by using refer and recording techniques (2) data analysis phase used qualitative methods and descriptive analytic techniques, and (3) data analysis phase using formal and informal methods. The results of this study are unfolding structures that build Babad Blahbatuh including text form, content, and function contained. The structure contained in Babad Blahbatuh cover form structure and narrative. The structure forms in this study include Babad text form, type and variety of language. Narrative structure includes flow, incident, character and characterization, setting, theme and mandate further. Functions of Babad historically describes the genealogy of Ki Gusti Jelantik from the past to the present. Religious functions have values ??that are believed to be related to the ceremony, ceremonial equipment, sayings and mantras contained in Babad. The function describes the genealogical pedigree or descendants of  Ki Gusti Ngurah Jelantik I-XX where descendants of Ki Gusti Jelantik must maintain and continue its Kawitan to the offspring in the future. This study is expected to be disseminated to the public to improve public knowledge of the struggle of the ancestors history and as an appreciation of cultural or traditional works to increase and maintained its existence